Optimalisasi Konten Promosi Digital melalui Inovasi Sederhana untuk Peningkatan Daya Saing UMKM: (Studi Kasus Komunitas Alisa Khadijah ICMI Ranting Tambun Selatan) - Toha Maksun; Sudarsih, Sudarsih; Aep Saepudin; Sumarno, Sumarno (Jurnal Visi Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, playing a role not only in job creation but also in maintaining national economic stability. However, amidst the rapid development of the digital era, MSMEs face significant challenges in adopting technology to expand market reach and increase the competitiveness of local products. This research seeks to identify and develop simple innovations in designing effective digital promotional content, with a case study of the Alisa Khadijah Community of the ICMI South Tambun Branch. The analysis focuses on the actual conditions of MSMEs, the application of simple innovations in business processes and products, and digital promotional strategies that suit the characteristics of modern consumers. Through surveys and observations, it was found that the use of quality visuals, interactive elements, narrative storytelling, and internal collaboration can have a positive impact on increasing consumer visibility and engagement. The results show that most MSMEs that implement this content strategy experience a significant increase in digital interactions and product sales in a relatively short time. Furthermore, collaboration with the Cooperatives & MSMEs Office and educational institutions is a crucial factor in accelerating digital transformation, as it can provide access to technical assistance and training. Based on these findings, this study recommends the formation of innovation teams at the community level, the holding of ongoing workshops, and the development of collaborative platforms to share best practices and develop business networks. With the right approach, MSMEs can not only adapt to the digital era but also have the potential to expand their business scale and increase their competitiveness in the global market, thereby further strengthening their contribution to the Indonesian economy. This study recommends the formation of innovation teams within communities, practical workshops, and the development of collaborative platforms to increase MSME competitiveness in the digital market.